A calculus of the absurd

4.3 Quadratics

The quadratic formula 1212 This is the result of completing the square for \(ax^2 + bx + c\) and using it solve the equation \(ax^2 + bx + c = 0\) for \(x\) states that for a quadratic \(ax^2 + bx + c = 0\),

\begin{equation} \label {the quadratic formula} x = \frac {-b \pm \sqrt {b^2 - 4ac}}{2a} \end{equation}

The \(b^2 - 4ac\) gives quite a bit of information away. It’s called the "discriminant", and sometimes written as \(\Delta \).

If \(b^2 - 4ac > 0\) then we have exactly two solutions to the quadratic.

If \(b^2 - 4ac = 0\) (which also means that \(\sqrt {b^2 - 4ac} = 0\)), then there will only be one solution (because adding zero does nothing 1313 This is often handy for algebraic manipulation. - see the equation directly below for details).

\begin{equation*} \frac {-b \pm \sqrt {b^2 - 4ac}}{2a} = \frac {-b}{2a} \text { if $b^2 - 4ac = 0$} \end{equation*}

If \(b^2 - 4ac < 0\) then there are no real solutions to the quadratic.